MicroRNA-33a levels do not correlate with the expression of its host gene SREBF2 and its isoforms in prostate cancer cell lines - Karataş, Ömer Faruk; Ittmann, Michael (The European Research Journal, 2018)
Objectives. Prostate cancer is currently the most frequently diagnosed malignant neoplasm and the second leading cause of cancer related mortality in men over the age of 50 years in the developed countries. MicroRNA-33a (miR-33a), localized within the intron 16 of SREBF2, has been reported to have tumor suppressive properties in some cancers including prostate cancer, whereas its host gene, SREBF2, has been shown to be elevated in prostate cancer and to act as an oncogene. Due to the paradoxical expression of an oncogene and a tumor suppressor from a single genetic locus, there is a need for evaluation of miR-33a and SREBF2 expression status in prostate cancer cells to help understanding their roles in prostate carcinogenesis. Methods. In this study, we aimed at investigating the link between the expressions of miR-33a and its host gene SREBF2 and its isoforms in prostate cancer cell lines using quantitative real time PCR. We evaluated the relative expression levels with using 2- ΔΔCT method and tested the correlations of microRNA and gene expressions with Pearson’s Correlation test using GraphPad Prism 6. Results. Our results demonstrated variable expression levels for SREBF2 mRNA and miR-33a expression levels in prostate cancer cell lines, with some decreased, some increased and some unchanged. Further analysis showed a strong correlation among expressions of SREBF2 isoforms though we could not find a significant association between levels of SREBF2 isoforms and miR-33a expression. Conclusion. This data suggest possible posttranscriptional regulation of miR-33a expression in prostate cancer.